Criminal Law Policy in Tackling Fake News Crime - Aulia Aninda Ektya Putri; Querida Paraninda Pandan Arum; Tasya Della Sabena; Viola Puti Saptafasya; Jannah Tanzela Andika Yahya (Proceeding International Conference Restructuring and Transforming Law, 2024)
Criminal acts of spreading false information or hoaxes have become a serious threat in the rapidly evolving digital information era. To combat this phenomenon, criminal law policy plays a central role. This journal discusses the role and importance of criminal law policy in addressing the crime of spreading false information. This research employs a non-doctrinal approach in the study of criminal law, meaning that it relies not only on legal provisions but also emphasizes the views of criminal law experts, both domestically and internationally. This approach aims to gain a clear understanding and a comprehensive overview of the issues examined in this research. The research findings indicate that criminal law policy plays a crucial role in addressing the crime of spreading false information. However, law enforcement against this crime in Indonesia still faces various challenges, such as difficulties in determining the boundaries between freedom of expression and the dissemination of false information, lengthy and complex legal processes, and the influence of corruption and nepotism within the legal system. Therefore, efforts are needed to enhance the resources of law enforcement agencies, combat corruption, improve transparency, and raise public awareness of the law.